Desconsideração da personalidade jurídica - Gonçalves, Eveline Berto (2016)
The theory disregard of legal entity over time has been gaining strength and today has become essential to combat fraud, however, currently its application takes place through case law and interpretation of the judge. The theory faced major barrier in the world and in Brazil, in the design of the property autonomy of the legal entity, according to which the assets of legal entities should not be confused with the partner that part, which in a few times, leads to the misuse of the legal entity, leading to unfair results, so that they began to speak of the possibility of disregarding the legal entity so. Despite currently exist forecasts expressed about the disregard of legal personality and assumptions to apply it, there was still omission on the procedibilidade of disregard of legal entity, which with the enactment of Law 13.105 / 2015 which entered into force on 03/18/2016 day, he tried to fill this gap, establishing procedural rules for their application